2018
DOI: 10.4103/jehp.jehp_7_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of educational package on sexual function in cold temperament women of reproductive age

Abstract: INTRODUCTION:Sexual health is one of the key factors to sustain marital life and having a good sexual function. On the other hand, temperament affects sexual function. Training is also one of the basic foundations for promoting sexual health. Therefore, the researcher has designed and implemented a study (2017) aimed “determining the study of educational package on sexual function in cold temperament women of reproductive age.”METHODS:This randomized clinical trial study was performed on 80 women in two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Accordingly, the data suggested that providing sexual function package could change sexual desire dimensions, sexual excitement, the lubrication of the vagina, orgasm, sexual satisfaction, sexual pain, and overall sexual function score (Baradaran-Akbarzadeh et al, 2018). This result is in line with that of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, the data suggested that providing sexual function package could change sexual desire dimensions, sexual excitement, the lubrication of the vagina, orgasm, sexual satisfaction, sexual pain, and overall sexual function score (Baradaran-Akbarzadeh et al, 2018). This result is in line with that of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Sexual function and all its dimensions were improved after intervention in the intervention group. [ 57 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many symptoms of this dystemperament are consistent with conditions of unknown etiology in conventional medicine, including weakness and fatigue. PM sources recommend practical measures to correct cold-wet dystemperament or to treat related diseases, supported by primary evidence (42,43). Diagnosing cold-wet Mizaj in individuals and recommending preventive measures accordingly will help reduce the occurrence of diseases associated with cold-wet Mizaj (27,35,(42)(43)(44)(45)(46).…”
Section: Introductionmentioning
confidence: 99%